Evaluation of Macro Nutrition in Some Hybrid Clones of Eucalyptus spp. on Andisol and Inceptisol Soil in North Sumatra - Sinurat, Darwin; Hanum, Hamidah; Rahmawati, Nini; prit, Kanvel; Hutagaol, Adventris (Journal of Sylva Indonesiana, 2024)
Eucalyptus spp. is one of the most widely planted genera for pulp and paper industrial forests (Hutan Tanaman Industri/HTI) in the world, specifically in Indonesia, due to its productivity and wood properties. The growth and productivity of eucalypts in North Sumatra depend on the type of soil and the clone used. The purpose of this study was to look at the macronutrient content in different soil types and to evaluate the macronutrient content in plant biomass with different clones to keep the nutrient conditions in the soil maintained. This research was conducted at 3 of the eucalyptus plantation sector in North Sumatera with hybrids of eucalyptus clones that were 48 months old. Height, diameter breast height (DBH), and survival data were taken. Wood, leaf, bark, and soil samples were taken for nutrient analysis in the laboratory. The results showed that there were differences in soil macronutrients (N, P, K, Mg, and Ca) among the three types of soil. The average growth also showed a significant difference in growth in each soil order. There were differences in nutrients in plant biomass for the clones tested, and there were differences in nutrients in each part of the plant biomass. Wood and bark that were taken from the tree while harvesting had a greater amount than the biomass that stays in the field (leaf and branch). The different fertilization regimes in the research area are one way to increase the productivity of eucalyptus plants in the field